Landscape management for sustainable supplies of bioenergy feedstock and enhanced soil quality - Karlen, Douglas L.; Muth Jr., David J. (Agrociencia Uruguay, 2012)
Agriculture can simultaneously address global food, feed, fiber, and energy challenges provided our soil, water, and air resources are not compromised in doing so. As we embark on the 19th Triennial Conference of the International Soil and Tillage Research Organization (ISTRO), I am pleased to proclaim that our members are well poised to lead these endeavors because of our comprehensive understanding of soil, water, agricultural and bio-systems engineering processes. The concept of landscape management, as an approach for integrating multiple bioenergy feedstock sources, including biomass residuals, into current crop production systems, is used as the focal point to show how these ever-increasing global challenges can be met in a sustainable manner. Starting with the 2005 Billion Ton Study (BTS) goals, research and technology transfer activities leading to the 2011 U.S. Department of Energy (DOE) Revised Billion Ton Study (BT2) and development of a residue management tool to guide sustainable crop residue harvest will be reviewed. Multi-location USDA-Agricultural Research Service (ARS) Renewable Energy Assessment Project (REAP) team research and on-going partnerships between public and private sector groups will be shared to show the development of landscape management strategies that can simultaneously address the multiple factors that must be balanced to meet the global challenges. Effective landscape management strategies recognize the importance of nature’s diversity and strive to emulate those conditions to sustain multiple critical ecosystem services. To illustrate those services, the soil quality impact of harvesting crop residues are presented to show how careful, comprehensive monitoring of soil, water and air resources must be an integral part of sustainable bioenergy feedstock production systems. Preliminary analyses suggest that to sustain soil resources within the U.S. Corn Belt, corn (Zea mays L.) stover should not be harvested if average grain yields are less than 11 Mg ha-1 (175 bu ac-1) unless more intensive landscape management practices are implemented. Furthermore, although non-irrigated corn grain yields east and west of the primary Corn Belt may not consistently achieve the 11 Mg ha-1 yield levels, corn can still be part of an overall landscape approach for sustainable feedstock production. Another option for producers with consistently high yields (> 12.6 Mg ha-1 or 200 bu ac-1) that may enable them to sustainably harvest even more stover is to decrease their tillage intensity which will reduce fuel use, preserve rhizosphere carbon, and/or help maintain soil structure and soil quality benefits often attributed to no-till production systems. In conclusion, I challenge all ISTRO scientists to critically ask if your research is contributing to improved soil and crop management strategies that effectively address the complexity associated with sustainable food, feed, fiber and fuel production throughout the world.